Properties of heat-treated sisal fiber/polylactide composites. (June 2015) - Huang, Can-Jun; Li, Xiang-Li; Zhang, Ye-Qing; Feng, Yan-Hong; Qu, Jin-Ping; He, He-Zhi; Shen, Han-Zhi
Sisal fibers (SFs) were pretreated by heat treatment (HT). The SFs were mixed with a biodegradable material, polylactide (PLA), and the composites were prepared by hot press molding. The effects of the HT temperature and time on the mechanical properties of the composites were investigated, and the HT mechanism was studied by scanning electron microscopy and infrared, x-ray photoelectron, and nuclear magnetic resonance spectroscopies. The results show that an appropriate HT can remove strongly hydrophilic materials such as hemicelluloses from the fibers, and thus decrease their hydrophilicity, thereby improving the retting between the fibers and the matrix. This improves fiber–matrix interfacial adhesion, which can improve the mechanical properties of the composites. The HT also influences the fiber strength to some extent and affects the mechanical properties of composites.